Verification of scholars and references in Islamic websites - Mahmud, Murni; Muhammed Nasser, Rasheed; Md. Tap, Abu Osman (IIUM Press, 2011)

(untitled)
Websites is a corpus of infonnation and content on various domains of topics and subjects; however, they may lack of appropriate references or reliable sources. References and sources in websites may include book, articles, scholars' speech, text etc. Many users consider websites, as an important source of knowledge; therefore there is a need for a tool that helps users to evaluate the correctness and validity of the references and scholars referred in the websites. The tool should assist the users to verify if the websites that being referred has provided good and reliable references. Verification of references and sources is highly critical in Islamic websites as the content may guide to the correct religious practices. For this specific reason, the researchers develop a tool called I-WISER. It analyses the content in Islamic websites and generate a list of reference books and scholars names being used and referred in the websites. Relational content analysis methodology has been used to evaluate the website content regarding specific Islamic concepts. The relational content analysis method use verification concepts from database, and records certain score for each concept found within intended website. The report generated by I-WISER will provide a preliminary reflection ofthe quality of the content.